Inducing Linguistic Networks from Historical Corpora: Towards a New Method in Historical Semantics - Mehler, Alexander; Schwandt, Silke; Gleim, Rüdiger; Ernst, Alexandra (New Methods in Historical Corpora, 2013)
et al, tbk. Corpus linguistics and Interdisciplinary perspectives on language (CLIP). Tübingen: Narr, 2012.
Keywords: Linguistic Networks; Network Extraction from Text; Semantic Networks